2019
DOI: 10.1182/blood-2019-124653
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sevuparin, a Novel Non-Anti-Coagulant Heparinoid, in Patients with Acute Painful Vaso-Occlusive Crisis; A Global, Multicenter Double-Blind, Randomized, Placebo-Controlled Phase 2 Trial (TVOC01)

Abstract: Background and purpose: There are no currently approved treatments for the vaso-occlusive crises (VOC) associated with sickle cell disease (SCD). In addition to causing pain, vaso-occlusion and the resulting hypoxia cause a reduction in overall life expectancy and increase chronic morbidity. Sevuparin is a novel, non-anticoagulant, low-molecular weight heparin analogue, with a preclinical multi-modal activity profile against VOC relevant targets (i.e. P- and L-selectin, thrombospondin, Von Willebrand factor, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…It failed to show benefit in treating VOEs, although it was shown to prevent VOEs and to normalize blood flow in animal studies. 30 Both drugs were ineffective at treating VOEs and accelerating recovery, in agreement with the concept that P-selectin inhibition is not an effective strategy after a VOE has set in. Recently, crizanlizumab-a monoclonal antibody that inhibits P-selectin functionwas studied for its prophylactic use and yielded positive results that led to regulatory approval.…”
Section: Dovepresssupporting
confidence: 69%
“…It failed to show benefit in treating VOEs, although it was shown to prevent VOEs and to normalize blood flow in animal studies. 30 Both drugs were ineffective at treating VOEs and accelerating recovery, in agreement with the concept that P-selectin inhibition is not an effective strategy after a VOE has set in. Recently, crizanlizumab-a monoclonal antibody that inhibits P-selectin functionwas studied for its prophylactic use and yielded positive results that led to regulatory approval.…”
Section: Dovepresssupporting
confidence: 69%
“…This compound has been shown to be a potent anti-adhesive agent, both in in vitro and in vivo studies, which is crucial in the context of VOCs in SCD. It helps prevent or reduce blood vessel obstruction, a common phenomenon in this condition due to the abnormal adherence of sickle cells to each other and vessel walls [ 66 , 67 ]. Lizarralde-Iragorri, Parachalil Gopalan, Merriweather, Brooks, Hill, Lovins, Pierre-Charles, Cullinane, Dulau-Florea, Lee, Villasmil, Jeffries, and Shet [ 36 ] investigated the effectiveness of isoquercetin in reducing inflammation associated with blood clots (thromboinflammation) in SCD.…”
Section: Review Of Randomized Double-blind Clinical Trials For Sickle...mentioning
confidence: 99%
“…Sevuparin, a derivative of LMW heparin, which retains the P-selectin-binding domain of heparin but largely lacks anticoagulant properties, binds to P-and L-selectins, thrombospondin, fibronectin, and von Willebrand factor, inhibits the adhesion of sickle RBCs to stimulated cultured endothelial cells in vitro, and prevents vaso-occlusion with normalization of blood flow in a mouse model of vaso-occlusion 102 . A recently completed randomized, double-blind, placebo-controlled trial found that, although safe, sevuparin did not significantly reduce the time to resolution of vaso-occlusive crisis 103 . A phase II feasibility study of therapeutic-dose unfractionated heparin (NCT02098993) was recently terminated for poor enrollment, but a phase III, randomized, placebo-controlled study of tinzaparin in acute chest syndrome is ongoing (NCT02580773).…”
Section: Allosteric Modification Of Sickle Hemoglobin To Its High-oxygenmentioning
confidence: 99%